Multi-proxy analysis of sediment cores from Lago Rogaguado and Llanos de Moxos - Giesche, Alena; Lombardo, Umberto; Finsinger, Walter; Veit, Heinz (PANGAEA, 2020)
Lago Rogaguado is a large (315 km²) shallow lake in the Llanos de Moxos, Bolivian Amazon. Two Holocene-age lake sediment cores (1.25 and 1.5 m long) were collected using a UWITEC gravity surface corer and Livingstone piston corer in 2012 and 2013. The location of core LR-400 is 2 km from the western shoreline at 2.5 m water depth, whereas core LR-398 is in the center of the lake approximately 4 km from the nearest shoreline at 2.9 m water depth. Both cores were dated using ¹⁴C, and produced a multi-proxy dataset (XRF, bulk density, grain size, C:N, biogenic silica, water content, and macroscopic charcoal) that we used to uncover palaeoenvironmental changes in the context of vegetation changes (deduced from pollen analyses of core LR-400; Brügger et al., 2016). The objective of the dataset was to reconstruct long-term paleoenvironmental conditions around the lake, including lake levels, erosion and sedimentation rates, and local biomass burning for the Holocene.
Keywords: Bolivian Amazon; climate; Lake level; land use change; Llanos de Moxos; Shallow lake